– Application of Land Information Systems (LIS) To Evaluation and Planning Land Ownership in Gaza Strip – Geoplanning Study : تطبيق تقنية نظم معلومات الأراضي (LIS) لتقييم وتخطيط ملكيات أراضي قطاع غزة – دراسة جيوتخطيطية – - Shadi Zuhair Mohammed Kuhail (Journal of engineering sciences and information technology, 2019)
This study aimed to apply Land Information Systems (LIS) technology to evaluate and plan the properties of the Gaza Strip lands by tracking changes in the spatial and relative distribution of properties using GIS applications. In addition to identifying the land plots that are considered the most suitable for future urbanization, study showed that there is a time series of legislation In which the ownership of the land was transferred and the land distribution of the land as it is now. The study showed the role of LIS as one of the most important branches of geographic information systems, which is the best technique used in property management and classification. study showed that the use of land information systems cannot be dispensed with because it contributes to making the right decision before allocating land by analyzing future needs and linking them to the change in property distribution. The study showed that the use of cartographic modeling to arrive at determining the appropriate vouchers to guide future urbanization is more efficient than traditional methods. study resulted in the preparation of a database on land ownership at the sector level. The total area of ​​the government lands until the end of 2018 was about 55.9 km2, the land of the citizens of 304.1 km 2 and the lands of the endowments 4.9 km 2 of the total area of ​​the Gaza Strip of 365 km 2 and the historical development of properties on maps Through the use of statistics and tables of the Land Authority to track the spatial change in vouchers and the reasons that contributed to the decline of government properties so quickly. recommends study need for good planning in the decision-making institutions for the allocation of land for expansion projects and taking into account the criteria of local allocations due to the limited planning area of ​​the study area, which is one of the highest densities of the population in the world.